2009
DOI: 10.1063/1.3119640
|View full text |Cite
|
Sign up to set email alerts
|

Surface magnetization in non-doped ZnO nanostructures

Abstract: We have investigated the magnetic properties of non-doped ZnO nanostructures by using ab initio total energy calculations. Contrary to many proposals that ferromagnetism in non-doped semiconductors should be induced by intrinsic point defects, we show that ferromagnetism in nanostructured materials should be mediated by extended defects such as surfaces and grain boundaries.This kind of defects create delocalized, spin polarized states that should be able to warrant longrange magnetic interactions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…The six oxygen atoms contribute, but the two times coordinated oxygen atoms exhibit larger magnetic moments, while the closest zinc and oxygen atom neighbors contribute in a minor quantity. Dalpian et al have proposed that magnetism in non-doped ZnO systems arise from a delocalized surface state [16]. In agreement with their work, we find that the magnetic state is found at the surface, and that is only found when there is some kind of order inside the cluster.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The six oxygen atoms contribute, but the two times coordinated oxygen atoms exhibit larger magnetic moments, while the closest zinc and oxygen atom neighbors contribute in a minor quantity. Dalpian et al have proposed that magnetism in non-doped ZnO systems arise from a delocalized surface state [16]. In agreement with their work, we find that the magnetic state is found at the surface, and that is only found when there is some kind of order inside the cluster.…”
Section: Resultssupporting
confidence: 89%
“…The magnetism of these systems has been attributed to oxygen vacancies, zinc vacancies, intrinsic defects and interstitials. Of particular relevance to this work, Dalpian and co-workers have recently studied the magnetic properties of non-doped ZnO clusters, and claim that ferromagnetism should be mediated through extended surface states, since no single kind of defect is found to be responsible of the obtained magnetic moment [16]. Also, Coey et al suggest a chargetransfer mechanism from the core of the nanocrystal to its surface to explain ferromagnetism in oxide nanoparticles [17].…”
Section: Introductionmentioning
confidence: 96%
“…12 In addition, there are several calculations that suggest that ZnO nanocluster may be ferromagnetic without TM dopants. Schoenhalz et al 13 have proposed that the surface states promoted by extended defects ͑e.g., grain boundaries͒ may play an important role in mediating ferromagnetic interaction in such materials. A recent firstprinciples study of ZnO nanostructures coated with ligands containing N and S also reported FM due to the redistribution of charge promoted by ligand capping.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, nanoparticles have received attention with articles showing pure oxides [12][13][14][15][16][17][18][19] or oxides coated with thiols or amines [20][21][22] to display ferromagnetic behavior at room temperature. However, there is a mixture of techniques employed to produce the particles which could result in changes in stoichiometry, morphology and/or structure of the nanoparticles that may affect the observed magnetic behavior.…”
Section: Introductionmentioning
confidence: 99%